The Use of Religious Issues in Election Campaigns: A Bibliometric Analysis - Priono, Rendi; Prakoso, Velandani; Mahyudin, Mahyudin; Tenorio, Christine Balatero (Jurnal Studi Ilmu Pemerintahan, 2024)
The politicization of religion in election campaigns has become a global phenomenon with significant implications for voter behavior and democratic stability. This study aims to fill the gap in systematic understanding by conducting a bibliometric analysis of scholarly publications on religious issues in electoral contexts. Using data from the Scopus database (1980–2023), the study employs VOSviewer and RStudio to map publication trends, citation impact, geographical distribution, institutional contributions, and thematic networks. A total of 244 articles were analyzed, revealing a sharp increase in publications since 2000, with peaks in 2021. The United States and Indonesia emerged as dominant contributors, while Southeast Asian institutions showed strong local engagement. Thematic mapping identified “religious identity” and “voter behavior” as central themes, while topics like “digital religion” and “religious extremism” appeared as emerging or declining. The findings highlight the global relevance of religious discourse in political campaigns and its role in shaping polarization and identity politics. This study contributes to the academic field by offering a structured overview of the intellectual landscape and suggesting future research directions emphasizing cross-cultural collaboration and methodological innovation.